(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Recently prestressing take place at every field in civil engineering one of them is Prestressed Metro girder. Structures are subjected to two types of loading one is static and other dynamic. I- bridge girder are one of the principal type of cast-in-place girder with stressed tendons. The FEM is general method of structural analysis. A simple span I-girder was analyzed by using IRC class AA type loading as a one dimensional structure using FEM method. Analyze same girder as 3-dimentional structural using Finite element plate as beam element for main beam element for main beam using software STAAD pro Vi8.The detailed study is carried out for I-beam box girder and Rectangular box girder for the span 24m under IRC class AA loading condition.